PENGARUH SUPERVISI KEPALA SEKOLAH DAN KONSEP DIRI TERHADAP DISIPLIN KERJA GURU PNS: Studi kasus di SMP Negeri Se-Kota Cilacap, Jawa Tengah - Heni Rochimah; Rugaiyah Rugaiyah; Masduki Ahmad (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2018)
The objectives of this reseach are to study about the effects principal supervision and self-concept on work discipline of teachers of Civil Servants in State Junior High School of Cilacap Regency, Central Java. The reaseach was conducted by survey method with path analysis technique. The population in this study were civil servant teachers in State Junior High School of Cilacap Regency, while the respondets were 143 teacher selected randomly. The results are as follows: (1) there is a direct positive effect of principal supervision on teacher work discipline; (2) there is a positive direct effect of self-concept on teacher work discipline, and (3) there is a direct positive effect of principal supervision on self concept. Therefore, improvement of the teacher work discipline should be improved by enhaching the implementation of principal supervision and working standard in the school.